2021
DOI: 10.1029/2021ef002062
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Distributions of Urban Expansion in Global Watersheds

Abstract:  We quantify five features of urban expansion among 220 watersheds globally for the last 25 years  Most of watersheds globally experienced a decelerating and sprawling urban expansion  Rapid and low-density of urban expansion in endorheic watersheds may threaten their sustainability Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 73 publications
(155 reference statements)
1
0
0
Order By: Relevance
“…We wish to use the urban land cover from the same data source for consistency among this simulation and future experiments. The He2021 dataset is in broad agreement, in terms of total urban area and urban area growth rate, with previous urban land cover projections (Figure ; Chen et al, 2020; Gao & O’Neill, 2020; Huang et al, 2021; Li et al, 2019). The urban properties, including morphological, thermal and radiative characteristics, prescribed for the new surface dataset are the same with those in the J2010 dataset.…”
Section: Model and Experimentssupporting
confidence: 84%
“…We wish to use the urban land cover from the same data source for consistency among this simulation and future experiments. The He2021 dataset is in broad agreement, in terms of total urban area and urban area growth rate, with previous urban land cover projections (Figure ; Chen et al, 2020; Gao & O’Neill, 2020; Huang et al, 2021; Li et al, 2019). The urban properties, including morphological, thermal and radiative characteristics, prescribed for the new surface dataset are the same with those in the J2010 dataset.…”
Section: Model and Experimentssupporting
confidence: 84%
“…At the global scale, Chung et al (2021) revealed the interrelationships between global urban land and freshwater ESs. Huang et al (2021) analyzed urban expansion from 1992 to 2016 in terms of global endorheic and exoreic watersheds. At the national scale, Liu et al (2022) analyzed urban expansion and evaluated the relationships between supply of and demand for ESs in China.…”
Section: Introductionmentioning
confidence: 99%